Gender Difference in the Prevalence of Insomnia: A Meta-Analysis of Observational Studies - Zeng, Liang-Nan; Zong, Qian-Qian; Yang, Yuan; Zhang, Ling; Xiang, Yi-Fan; Ng, Chee H.; Chen, Li-Gang; Xiang, Yu-Tao (Frontiers in Psychiatry, 2020)
Objective Insomnia is a major health challenge in the general population, but the results of the gender differences in the epidemiology of insomnia has been mixed. This is a meta-analysis to examine the gender difference in the prevalence of insomnia among the general population. Methods Two reviewers independently searched relevant publications in PubMed, EMBASE, PsycINFO, Web of Science from their inception to 16 April 2019. Studies that reported the gender-based prevalence of insomnia according to international diagnostic criteria were included for analyses using the random-effects model. Results Eventually 14 articles were included in the meta-analysis. The pooled prevalence of insomnia in the general population was 21.1% (n=339,636, 95% confidence interval (CI): 17.2%-25.0%), and females had a significantly higher prevalence of insomnia compared with males (OR=1.74, 95% CI: 1.69, 1.79, Z=39.96, p<0.0001). Subgroup analyses showed that greater gender difference was associated with the use of case-control study design and consecutive sampling method. Meta-regression analyses also revealed that higher proportion of females and better study quality were significantly associated with greater gender difference. Conclusions This meta-analysis found that the prevalence of insomnia in females was significantly higher than males in the included studies. Due to the negative effects of insomnia on health, regular screening and effective interventions should be implemented in the general population particularly for females.